Representasi Muslimah Tangguh dalam Iklan Elzatta 'Hijab for Every You': Analisis Semiotika Roland Barthes - Qoniah Nur Wijayani; Darul Islam (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
Advertising in the contemporary Muslim fashion industry has evolved beyond mere product promotion into a powerful arena for the construction of social meaning, cultural identity, and gendered representation. This study investigates how resilient Muslim women are represented in the Elzatta